Determinação de metais e metaloides em tubarões lixa Ginglymostoma cirratum capturados no complexo estuarino de são marcos, e seus efeitos citotóxicos e genotóxicos - MARQUES, Mateus Brandão (2025)
Elasmobranch populations have experienced significant declines in recent decades due to anthropogenic activities, with chemical contamination comprising one of the five main threats to this group. Although some biochemical biomarkers are used to assess the health of these organisms, particularly concerning contamination by metals and metalloids, associations with genotoxic biomarkers remain scarce, especially for sharks along the Brazilian Amazon coast. In this context, this study assessed the nurse shark (Ginglymostoma cirratum) in the São Marcos Estuarine Complex, Maranhão, determining metal/metalloid and oxidative stress biomarker levels, such as reduced glutathione (GSH), glutathione S-transferase (GST), and metallothionein (MT), as well as nuclear anomalies (micronucleus, nuclear buds, and bilobed cells). Significant differences in metal and metalloid accumulation between males and females were observed but were not reflected in antioxidant responses. Higher concentrations of GSH and GST activity were found in the gills and liver, while MT concentrations were higher in the muscle. A low frequency of genotoxic damage was detected, attributed to certain life habits of nurse sharks, such as a sedentary lifestyle and an efficient DNA repair system. Several moderate to strong correlations between metals/metalloids and biochemical and genotoxic responses were observed, especially in females, highlighting the protective role of GST against DNA damage. The protective effect was observed only in the liver, where Se demonstrated its antagonistic action against Hg in both females and males. Complementing these findings, a narrative review emphasized the need to evaluate DNA integrity in elasmobranchs to identify environmental threats and support conservation efforts. The sensitivity of these organisms to pollutants highlights the importance of genotoxic biomarkers as key tools for monitoring impacts and mitigating risks in marine ecosystems. These results reinforce the relevance of integrated research to protect elasmobranchs in environments under anthropogenic impact and to promote their global conservation.